Verification of Soil Test Crop Response Based Calibrated Phosphorus for Food Barely (Hordeum Vulgare L.) Production in Sinana District, Bale Zone, Oromia Region, Southeast Ethiopia - Eshetu, Mulugeta; Regassa Gosa; Tesfaye Ketema; Girma Getachew (University of Jember, 2024)
Nitrogen and phosphorus are the main variables restricting crop productivity in the soil of the study area, especially, in food barely productions. In the Sinana district, soil test-based phosphorus calibration studies were carried out in the past, and fertilizer 46 N kg ha-1, P critical (20 ppm), and P requirement factor (4.60) were recommended for food barely production. To confirm the phosphorus critical (Pc) level and phosphorus requirement factor (pf) found during soil test crop response based phosphorus fertilizer calibration study for food barely production in 2022 bona (July to December) main cropping season, an on-farm field experiment was carried out in this study. The experimental setting comprised three treatments: (1) control (without fertilizer), (2) farmer practices as a blanket recommendation, and (3) soil test crop response-based phosphorus recommendation results. The improved food barely, Adoshe variety was used as a test using farmers as replication in seven sites with 10 m × 10 m plot sizes. Soil samples before planting were taken at 0 - 20 cm soil depth using a random sampling technique and analyzed using standard laboratory procedures. In contrast, the agronomic parameters were analyzed using R software 4.1.1 version. The results show soil sample analysis varied from 6. 03 to 6.25, 1.68 to 2.62%, and ranged from 1.01 to 3.30 mg/kg for soil pH (pH_H2O), OM, and available phosphorus, respectively. The results revealed a significant (p < 0.05) difference between food yield and yield components. The soil test crop response-based phosphorus recommendation results yielded the highest grain yield (5682.43 kg ha-1) with a marginal rate of return (4131.16%). Thus, for food barely production in Sinana District, the Pc (20 ppm) and pf (4.60) with optimal N (46 kg ha-1) were verified from this study. It should be recommended that further demonstrate and scale up the application of soil test-based fertilizer recommendations, to extrapolate Pc and Pf for similar soil types, and to determine the adjusted NPS fertilizer rate using calibrated phosphorus for food barely production.